Low Temperature Reaction of Molecular Zinc Oxide Precursors in Ionic Liquids Leading to Ionogel Nanoparticles with Shape Anisotropy. Issue 1 (15th November 2016) - Voggenreiter, Markus; Vöpel, Pascal; Smarsly, Bernd; Polarz, Sebastian
Abstract : The majority of particle synthesis methods are based on nucleation and growth processes in solvents. Whereas the role of capping agents has been investigated extensively regarding control particle size and shape, the unique role of the solvent is understood to a much lesser extent. Compared to other polar solvents, e.g. water, ionic liquids (ILs) are unique because their properties can be fine‐tuned precisely by appropriate choice and modification of cation and anion. This makes ILs also interesting for particle synthesis. We present the generation of zinc oxide (ZnO) in imidazolium ILs starting from molecular precursors. A hydrolytic, sol‐gel based synthesis route is suitable to achieve nanocrystalline ZnO. We find by in‐situ synchrotron wide angle X‐ray diffraction that in ILs an unusual ZnO phase with α‐boron nitride structure acts as an intermediate prior to crystallization of the thermodynamically stable Wurtzite. This special mechanism leads to organic‐inorganic hybrid IL/ZnO nanoparticles with plate‐like morphology. Because of the large content of IL embedded in the ZnO matrix the novel particles gain ionogel properties, e.g. ion conductivity probed by impedance spectroscopy. Abstract :